Development of Augmented Reality Video Media to Improve Mastery of Tahiat Arabiya Arabic Language Course Students - Masriah, Masriah; Kusnawati, Yanti (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study aims to develop Augmented Reality (AR) based learning media in the form of videos to improve the mastery of Tahiyyat Arabiyah vocabulary in students who take Arabic language courses. This media is designed to help students understand and memorize Arabic mufrodat more interactively and interestingly through the use of AR technology. The development model used in this research is ADDIE, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects involved early semester students of Arabic language courses at Institut Agama Islam Negeri Sheikh Nurjati Cirebon, with the participation of 53 students in the initial survey and 33 students and seven lectures in the product trial. The results showed that the use of AR video contributed significantly in improving the mastery of Arabic vocabulary, especially those related to Tahiyyat Arabiyah. Students who used this media showed improvement in terms of vocabulary mastery and proper pronunciation. In addition, AR video was considered very effective in terms of visual appearance and ease of use. Respondents rated this media as able to increase learning motivation and provide a more interactive learning experience compared to traditional methods. However, there are some technical challenges, such as device compatibility that only supports the Android system. This research makes a new contribution in the context of Arabic language learning and shows that AR technology has great potential to be adopted in foreign language learning more widely.